New Negotiation Concept of the Artsakh Settlement: Values Matter Everything - Galstyan, Khachik (YSU Journal of International Affairs, 2023)
The article discusses the regional status quo, formed after the last large-scale military aggression of Azerbaijan against Artsakh and Armenia, as well as its impact on the settlement of the Artsakh conflict. The main goal of the study is to reveal the value significance of Artsakh for the main actors of the conflict and to demonstrate the evolution of value transformations in understanding the essence of the conflict in the socio-political discourses of Azerbaijan and Armenia. The author substantiates the hypothesis that values have a decisive importance in forming negotiation positions in the context of conflict resolution. Furthermore, negotiating parties not only base negotiations on certain values but also form different value preferences concerning the subject of the conflict. In particular, it is shown that after the victory in the first Artsakh war there were tendencies to reduce the importance of Artsakh in the socio-political discourse of Armenian society. On the contrary, the value level of perception of the conflict has significantly increased among the Azerbaijani public. The author puts forward the notion that for the full and effective functioning of the project of Armenian statehood, it is necessary to once again raise the value of Artsakh. This issue is vital for implementing the new national security strategy and establishing an appropriate negotiating concept in the resolution of the Artsakh conflict.
Keywords: Artsakh conflict; post-war status-quo; negotiation concept; value red lines; border values